Discussion on Some Recent Order-Theoretic Metrical Coincidence Theorems Involving Nonlinear Contractions. (30th March 2016) - Alam, Aftab; Khan, Qamrul Haq; Imdad, Mohammad
Abstract : We prove some coincidence theorems involving a pair of self-mappings f and g defined on an ordered metric space X wherein f is g -increasing φ -contractive mapping. In our results, neither the whole space X nor the range subspaces (f ( X ) or g ( X ) ) are required to be complete. Instead, we use the completeness of a subspace of X satisfying suitable conditions.